Integrasi Ethnopedagogi dalam Pembelajaran Kompetensi Interkultural Prancis-Indonesia - Sri Handayani; Dwi Astuti (Universitas Lambung Mangkurat, 2026)
Understanding and mastering both Indonesian and French cultures are essential prerequisites for preparing learners to become locally rooted citizens with a global outlook. However, the low level of French-language literacy among students at UNNES raises concerns about their limited comprehension of both their own culture and French culture. This study aims to analyze the integration of ethnopedagogy into French language learning from an intercultural perspective. To achieve this objective, a case study was conducted through interviews with 14 French lecturers at Universitas Negeri Semarang. The interviews provided insights into the acquisition of intercultural competence at this institution in the Indonesian context and highlighted the importance of incorporating ethnopedagogy into language learning and focusing on the integration of ethnopedagogy into Franco-Indonesian intercultural learning. The results show that this integration relies primarily on grounding teaching content in local values and culture. This is particularly evident in the choice of teaching materials, teaching strategies, and the formulation of learning objectives. Integrating local cultural values into intercultural learning not only strengthens students' appreciation of their cultural heritage but also develops their ability to engage critically with French culture. The findings can serve as a reference for lecturers in designing teaching resources and selecting learning strategies adapted to the local context, while simultaneously fostering the development of critical intercultural literacy in the teaching of French as a foreign language.